On a multivariate generalization of the covariance. Issue 9 (3rd May 2017) - Díaz, Walter; Cuadras, Carles M.
ABSTRACT: Hoeffding's lemma provides a representation of the covariance of two random variables in terms of the difference between the joint and marginal distributions. This article proposes a multivariate generalization of the covariance between functions of bounded variation in the semialgebra of rectangles on . Some applications include the covariance inequality among functions where the variables are positive orthant dependent.